1975
DOI: 10.1073/pnas.72.4.1630
|View full text |Cite
|
Sign up to set email alerts
|

Purine metabolism in murine virus-induced erythroleukemic cells during differentiation in vitro.

Abstract: Purine metabolism was studied in murine virus-induced erythroleukemic cells stimulated to differentiate in vitro in the presence of dimethylsulfoxide. The activities of the enzymes that catalyze the synthesis of the first intermediate of the de novo purine pathway, phosphoribosyl-1-amine, were decreased while the enzymes that catalyze the conversion of purine bases to purine ribonucleotides remained unchanged at the time the cells acquired the specialized function of hemoglobin synthesis. In addition, cytidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…5 B). MEL cells treated with hemin display a rapid (within~6 h) increase in globin mRNA (22,41,51), but do not show changes characteristic of terminal differentiation (22), such as limited proliferative capacity (i.e., commitment ; 12, 21), induction of cytidine deaminase activity (46), or induction of the chromatin-associated protein, IP2 5 (24). Our observations show that the precipitous decline in vimentin mRNA is an early event in MEL cell differentiation, and this event precedes, but may be associated with commitment to terminal differentiation .…”
Section: Relationship Of Vimentin Mrna Repression To Commitment Of Mementioning
confidence: 99%
See 1 more Smart Citation
“…5 B). MEL cells treated with hemin display a rapid (within~6 h) increase in globin mRNA (22,41,51), but do not show changes characteristic of terminal differentiation (22), such as limited proliferative capacity (i.e., commitment ; 12, 21), induction of cytidine deaminase activity (46), or induction of the chromatin-associated protein, IP2 5 (24). Our observations show that the precipitous decline in vimentin mRNA is an early event in MEL cell differentiation, and this event precedes, but may be associated with commitment to terminal differentiation .…”
Section: Relationship Of Vimentin Mrna Repression To Commitment Of Mementioning
confidence: 99%
“…Exposure to a variety of chemical agents, such as dimethyl sulfoxide (DMSO), hexamethylene-bisacetamide (HMBA), or butyric acid induces MEL cells to differentiate (14,29,48; for a review see reference 35). Among the characteristic phenomena observed during terminal differentiation ofMEL cells are a maturation from a basophilic erythroblastic appearance to an orthochromatophilic normoblastic phenotype (14), a loss of proliferative capacity (12,21 ), alterations in purine metabolism (46), increases in iron uptake and heme synthesis (14), an elevation of heme synthetic enzyme activities (10,54), the induction of globin mRNAs (43,46,50), and the accumulation of hemoglobin (14). The tremendous induction of hemoglobin synthesis and accumulation in chemically-induced MEL cells, a distinctive feature of erythroid terminal differentiation in vivo, is effected by transcriptional activation of globin genes (2,34,44); the relative accumulation of globin mRNAs also may be modulated by the stabilization of these messages and/or by the destabilization of nonglobin rnRNAs (2,32,56,60).…”
mentioning
confidence: 99%
“…The latter, by liberating DNA from its complex relationships with chromosome proteins very likely creates ideal conditions for triggering activation of genes that control erythroid differentiation of MEL cells. It has indeed been suggested that DMSO promotes conformational changes in the protein molecules producing a relaxation in chromatin structure (Reem and Friend, 1975;Tanaka et al. 1975;Stratling, 1976), perhaps by disrupting hydrogen bonds (Preisler and Lyman, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is diverse experimental evidence to suggest a role for purine NTD metabolism in the control of cellular maturation. Studies with the Friend erythroleukemia cell line, for example, have shown that cellular maturation can be promoted by purine bases or purine analogues (hypoxanthine [Hx], 6-thioguanine, and 6-mercaptopurine) which inhibit NTD biosynthesis (10,11). It has also been observed that lymphoblastic, mono-and myeloblastic leukemia cells express abnormal activity levels of enzymes that regulate the intermediary metabolism of purine NTD, such as adenosine deaminase (12)(13)(14)(15), inosine monophosphate dehydrogenase (IMPD) (16), and 5'-methyl thioadenosine phosphorylase (17).…”
Section: Abstract In Studies With the Human Promyelocyticmentioning
confidence: 99%